Early Bilingualism Through the Looking Glass: Latino Preschool Children's Language and Self-Regulation Skills. (21st June 2017) - Melzi, Gigliana; Schick, Adina R.; Escobar, Kelly
ABSTRACT: During the early years, children's language skills are developing rapidly. For bilingual children, the development of both languages is highly sensitive to environmental input. Thus, capturing bilingualism in the early years poses a great challenge for researchers, especially those interested in examining how bilingualism might relate to other developmental areas, such as self-regulation. Traditionally, child development researchers have operationalized bilingualism as a categorical variable, most often relying on the use of self-reported data. In the present study, we compared various ways of capturing childhood bilingualism and demonstrated how these different measures privileged divergent aspects of children's bilingual experience, as well as how they were differentially related to children's self-regulation skills.